Improving Sperm Cryopreservation With Type III Antifreeze Protein: Proteomic Profiling of Cynomolgus Macaque (Macaca fascicularis) Sperm - Chen, Bingbing; Wang, Shengnan; Inglis, Briauna Marie; Ding, Hao; Suo, Angbaji; Qiu, Shuai; Duan, Yanchao; Li, Xi; Li, Shanshan; Sun, Wendell Q.; Si, Wei (Frontiers in Physiology, 2021)
Antifreeze protein III (AFP III) is used for cryopreservation of germ cells in various animal species. However, the exact mechanism of its cryoprotection is largely unknown at the molecular level. In this study, we investigated the motility, acrosomal integrity and mitochondrial membrane potential (MMP), as well as proteomic change of cynomolgus macaque sperm after cryopreservation. Sperm motility, acrosomal integrity and MMP were lower after cryopreservation (p < 0.001), but significant differences in sperm motility and MMP were observed between the AFP-treated sperm sample (Cryo+AFP) and the non-treated sample (Cryo-AFP) (p < 0.01). A total of 141 and 32 differentially-expressed proteins were respectively identified in cynomolgus macaque sperm cryopreserved without and with 0.1µg/ml AFP III compared to fresh sperm. These proteins were mainly involved in mitochondrial production of reactive oxygen species (ROS), glutathione (GSH) synthesis and cell apoptosis. The addition of AFP III in the sperm freezing medium resulted in significant stabilization of cellular molecular functions and/or biological processes in sperm, as illustrated by the extent of proteomic changes after freezing and thawing. According to the proteomic change of differentially-expressed proteins, we hypothesize a novel molecular mechanism for cryoprotection that AFP III may reduce the release of cytochrome c and thereby reduce sperm apoptosis by modulating the production of ROS in mitochondria. The molecular mechanism that AFP III acts with sperm proteins for cellular protection against cryoinjuries needs further study.